Implementation of relevant fourth industrial revolution innovations across the supply chain of fruits and vegetables: A short update on Traceability 4.0. (30th May 2023) - Hassoun, Abdo; Kamiloglu, Senem; Garcia-Garcia, Guillermo; Parra-López, Carlos; Trollman, Hana; Jagtap, Sandeep; Aadil, Rana Muhammad; Esatbeyoglu, Tuba
Graphical abstract: Highlights: Increased interest in the food traceability is driving development of advanced tools. The concept of "Traceability 4.0" is introduced in the sector of fruits and vegetables. Traceability 4.0 focuses on Industry 4.0 technologies to ensure digital traceability. AI, IoT, blockchain, and big data are among the main Traceability 4.0 enablers. Abstract: Food Traceability 4.0 refers to the application of fourth industrial revolution (or Industry 4.0) technologies to ensure food authenticity, safety, and high food quality. Growing interest in food traceability has led to the development of a wide range of chemical, biomolecular, isotopic, chromatographic, and spectroscopic methods with varied performance and success rates. This review will give an update on the application of Traceability 4.0 in the fruits and vegetables sector, focusing on relevant Industry 4.0 enablers, especially Artificial Intelligence, the Internet of Things, blockchain, and Big Data. The results show that the Traceability 4.0 has significant potential to improve quality and safety of many fruits and vegetables, enhance transparency, reduce the costs of food recalls, and decrease waste and loss. However, due to their high implementation costs and lack of adaptability to industrial environments, most of these advanced technologies have not yet gone beyond the laboratory scale. Therefore, further research is anticipated to overcome current limitations for large-scale applications.